Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1172/jci105980
|View full text |Cite
|
Sign up to set email alerts
|

Congenital dysfibrinogenemia: fibrinogen detroit

Abstract: A B S T R A C T A 17 yr old female with a congenital bleeding disorder was found to suffer from dysfibrinogenemia. Whole blood and plasma coagulation times were delayed and thrombelastograms were grossly abnormal. Clottability of plasma fibrinogen by addition of thrombin was not demonstrated during the 30 min test period. Fibrinogen was revealed by turbidometric and immunologic techniques. Other coagulation factors were present in normal amounts and prothrombin activation was normal. Patient's plasma inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
3

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 33 publications
2
23
0
3
Order By: Relevance
“…Clinical expression of the defect is variable, ranging from no clinical manifestations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), to bleeding (9,(12)(13)(14)(15)(16)(17)(18)(19)(20) and even thrombotic episodes (14,20,21). Wound dehiscence also has been reported (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical expression of the defect is variable, ranging from no clinical manifestations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), to bleeding (9,(12)(13)(14)(15)(16)(17)(18)(19)(20) and even thrombotic episodes (14,20,21). Wound dehiscence also has been reported (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal fibrinogens occurring in successive generations have been recognized in at least seven families (2)(3)(4)(5)(6)(7)(8). Abnormal fibrinogens inherited as dominants have been demonstrated (9,10) in two additional families originally reported as having congenital hypofibrinogenemia (11) and factor XIII deficiency (12).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal fibrinogens inherited as dominants have been demonstrated (9,10) in two additional families originally reported as having congenital hypofibrinogenemia (11) and factor XIII deficiency (12). The precise molecular defects of these abnormal fibrinogens remain unknown, although an amino acid substitution (arginine to serine) in the N-terminal portion of the a-(A)-chain (13) and a decreased content of carbohydrate (7) have been reported in one. A comparative study (9) of six of the abnormal fibrinogens (2-4, 6, 7, 11) suggested that at least five (2-4, 6, 7) are distinct.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, other inherited fibrinogen variants have been described (2)(3)(4)(5)(6)(7)(8)(9), and several previous reports (10,11) of hypofibrinogenemia are now believed to be qualita-tive rather than quantitative abnormalities. The clinical concomitants of these abnormal fibrinogens have varied greatly, ranging from no clinical symptoms to bleeding tendencies.…”
Section: Introductionmentioning
confidence: 99%